2005
DOI: 10.1111/j.0013-9580.2005.23804.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fractures among Epilepsy Patients: A Population‐based Retrospective Cohort Study in the General Practice Research Database

Abstract: Summary: Purpose:To compare the incidence of various fractures in a cohort of patients with epilepsy with a reference cohort of patients not having epilepsy.Methods: Patients were included in the epilepsy cohort if they had at least one diagnosis of epilepsy in their medical history and had sufficient evidence of "active" epilepsy (use of antiepileptic drugs, diagnoses) after the practice was included in the General Practice Research Database (GPRD). Two reference patients were sampled for each patient with ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
119
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(132 citation statements)
references
References 19 publications
2
119
1
10
Order By: Relevance
“…26 The greater fracture risk in that study may be at least partly explained by the severity of epilepsy because the study population included those with active epilepsy, with drugs or diagnosis codes recorded for .1 year. There are no previous studies comparing the risk of thermal injuries or poisonings between people with epilepsy and those without in the general population, so comparison of our findings with previous studies is not possible.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…26 The greater fracture risk in that study may be at least partly explained by the severity of epilepsy because the study population included those with active epilepsy, with drugs or diagnosis codes recorded for .1 year. There are no previous studies comparing the risk of thermal injuries or poisonings between people with epilepsy and those without in the general population, so comparison of our findings with previous studies is not possible.…”
Section: Discussionmentioning
confidence: 90%
“…[23][24][25] A prospective European study in .5-year-olds found no greater injury risk associated with epilepsy, 25 whereas a US study concluded that the risk of serious injuries in epilepsy is minor, 23 and a UK study using the Clinical Practice Research Datalink (CPRD) reported the risk of fracture in people with epilepsy to be twice that of those without epilepsy. 26 None of these studies focused on children and young adults with epilepsy; therefore, there is a lack of data for informing people with epilepsy about injury risk. We therefore investigated whether children and young adults with epilepsy are at greater risk of fracture, thermal injury, or poisoning than people without epilepsy and estimated the risk of injury #5 years after diagnosis with epilepsy.…”
mentioning
confidence: 99%
“…Proksimal ekstremite kırıkları ve torakal kırıklar güçlü kas kontraksiyonlarından kaynaklanırken, fasial kemik ve distal ekstremite kı-rıkları, kas kontraksiyonlarından ziyade indirekt travmaya bağlı olarak gelişmektedir. 2,3 Nöbet sonrası kırıkların bir kısmında kolaylaş-tırıcı neden olarak osteopeni ve osteoporoza neden olan metabolik ve antiepileptik kullanımı gibi iyatrojenik faktörler yer almaktadır. 4 Erkek cinsiyet, ileri yaş ve nöbet tipinin jeneralize tonik-klonik tipte olmasının kırık riskini artırdığı ve özellikle tanıyı takiben ilk yıllarda riskin daha yüksek olduğunu gösteren çalışmalar mevcuttur.…”
Section: Discussionunclassified
“…The most common musculoskeletal injuries seen after tonic clonic seizures include compression fractures of the thoracic and lumbar vertebral bodies, humeral head fractures/dislocations/combined injuries, manubriosternal joint disruption and femoral neck, pelvic, acetabular and scapular fractures (1,4,7,11). Less common fracture sites include the facial bones, odontoid process, ribs, distal radius and ankle (4,7,11,13). Bilateral posterior dislocation of the shoulder is highly suggestive of a seizure-related injury (7).…”
Section: Discussionmentioning
confidence: 99%